FAKTOR BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN - Retno Ayu Novitawati; Pinda Anggelina Henceni; R .Y Susanto (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
This study aims to see the effect of the marketing mix on consumer satisfaction, using descriptive quantitative with multivariate sampling technique. The data collected using questionnaires, surveys, documentation, and literature studies used with multiple linear regression. This study showed that simultaneously indicators of the marketing mix have a significant and positive effect on consumer satisfaction by 92.3%. The results showed that products and prices had no effect on satisfaction with significance level of 0.734 0.05, and 0.096 0.05, but places and promotion positive and significant effect on satisfaction with a significance level of 0.003 0, 05, and 0.000 0.05. From these results, it can be concluded to increase customer satisfaction. UKM must improve their marketing mix strategy.